The Effect Of Greeting Card Toward Students Writing Skill At The Eighth Grade Student Of Mts Daarul ‘Ulum Cihara Lebak In Academic Year 2021/2022 - Fitriyani Fitriyani; Riandi Riandi; Ari Fajria Novari (Journal of English Language Learning, 2022)
This research paper aims to know whether there is a significant effect of greeting card media toward students writing skill at eighth grade students’ of MTs Daarul ‘Ulum Cihara lebak in academic year 2021/2022. This research paper uses a quantitative approach and a quasi-experimental design. The sample selection technique is cluster random sampling; The researcher used class VIII A (25 students) as the experimental class and class VIII B (25 students) as the control class. In the data collection technique, the researcher gave a pre-test and post-test. In analyzing the data, the researcher used SPSS 25 statistical calculations and used the post-test results of both the control and experimental classes to analyze the hypothesis test. The researcher found that output SPSS on tablel 4.8. It could bel seleln that signification valuel (p-valuel) = 0.001 at pair 1 and 0.001 at pair 2. Thely arel < α = 0.05, melanwhilel H1 is accelpteld and HO is reljelcteld Therefore, the researcher concludes that there is a significant effect of greeting card media on students' writing skills.